A eficiência dos gastos públicos em saúde e educação para os municípios do Estado do Ceará – uma análise empírica dos períodos de 2007 a 2009 e 2012 a 2015 - Maximino, Luíza Maíte de Oliveira Martins (2018)
The efficient allocation of public resources, especially in the areas of health and education, is one of the greatest challenges for managers. This difficulty is observed more forcefully at the municipal level, since such entities have a high degree of dependence on transfers from constitutional transfers, which impairs their financial autonomy. The scope of this study is to analyze the level of efficiency of the public expenditures applied in health and education by the municipalities of the State of Ceará. The data provided by the municipalities of Ceará to the former Court of Audit of the Municipalities of the State of Ceará (TCM / CE), as well as the Social Development Index of Supply (IDS-O) (IDS-R), referring to the areas of health and education, provided by the Research and Economic Strategy Institute of Ceará (IPECE). All data are related to the interstices between 2007 and 2009 and 2012 to 2015. The analysis was based on a stochastic frontier econometric model with Cobb-Douglas production function, which had as input the ratio between the expenditure in the area examined and the total expense and as product the IDS-O or IDS-R, as the case may be. The technical efficiency scores, metrics used to compare the municipalities in the areas examined, were obtained. Among the results obtained, it was verified that, in both areas, there was no great variation of the technical efficiency of the expenses, over the years, when all the municipalities were analyzed. However, when examining the individual results of each entity, it was found that the majority of municipalities showed considerable variations in the results of technical efficiency during the years studied. In another round, when the years examined were divided into two periods, namely 2007 to 2009 and 2012 to 2015, and if one observed the ten most efficient municipalities and the ten least efficient ones per year of each interstice, there was a certain constancy of certain entities in such positions. The municipalities of Cruz, Groaíras, Sobral, Tururu and São Gonçalo do Amarante were positive highlights in education. Acarape, Alto Santo and Pacatuba occupied the last positions in that area. In terms of health, the best results were from São Gonçalo do Amarante, Porteiras and Brejo Santo. The worst places were with Umirim, Crato and Caucaia.